Localization of cholecystokinin-like immunoreactivity in the central nervous system of Triatoma infestans (Insecta: Heteroptera) - Settembrini, Beatriz Patricia (2008)
The distribution of cholecystokinin-like immunoreactivity was studied in the central nervous system of the heteropteran insect Triatoma infestans using high-sensitivity immunocytochemistry. In the protocerebrum, CCK-IR somata were observed in the anteromedial, anterolateral and posterior cell-body layers. The neuropils displayed different densities of immunoreactive neurites. Few immunoreactive somata were found in the optic lobe in both the medial and lateral soma rinds, as well as in the proximal optic lobe. Immunoreactive fibers were present in the medulla and lobula neuropils. The sensory deutocerebrum contained a higher number of immunopositive perikarya than the antennal mechanosensory and motor center. The antennal lobe glomeruli displayed a moderate density of immunoreactive fibers. With regard to the subesophageal ganglion, numerous CCK-IR somata were found close to the root of the mandibular nerve; others were present in the soma rind of the remaining neuromeres. CCK-IR perikarya were present in both thoracic ganglia, with the abdominal neuromeres containing the highest number of positive somata. The neuropils of both ganglia showed moderate densities of immunopositive processes. The distribution of CCK-LI in somata and neuropils of central nervous system of T. infestans is widespread suggesting that a CCK-like peptide may act mainly as a neuromodulator in the integration of information from distinct sensory receptors.